HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR BAHAN BANGUNAN SISWA KELAS X BANGUNAN DI SMK N 1 TANJUNG RAYA - 133-141 . Beni Febrianto (CIVED, 2013)
The purpose of this research is to determine the relationship the Motivation  Learning with Learning Result of Building Material at Class X in SMK N 1  Tanjung Raya. This research is a descriptive with correlational approach. The population on this research were all of students of clas X KB in SMK N 1 Tanjung Raya at academic year 2012/2013 is 69 of students. Total sampling techniques were used to get sampling until obtain the sample is 69 of students. The data of research obtained through a questioner what analyzed with pearson correlation techniques using SPSS version 15.0. This research revealed in general that the student motivation result is enough category and learning student result a class X at SMK N 1 Tanjung Raya is law category. Based on correlation result obtained rcount 0,354 > rtable  0,235 with significant alpa 0,003 < 0,05. It means there is a significant relationship between learning motivation with learning result in bilding material study class X SMKN 1 Tanjung Raya. Cooficient determibation 12,8% (law category). Key words : Motivasi Belajar, Hasil belajar, Mata Diklat Bahan Bangunan